2017
DOI: 10.1007/s00167-017-4442-9
|View full text |Cite
|
Sign up to set email alerts
|

More histologic and ultrastructural degenerative signs in the subscapularis tendon and the joint capsule in male patients with shoulder impingement

Abstract: PurposeThe purpose of the present study was to analyze biopsy samples from the subscapularis tendon and from the joint capsule from male patients with shoulder impingement syndrome (SAIS) and compare them with samples from male patients with post-traumatic recurrent shoulder instability. The hypothesis of the study was that patients with SAIS would have more histologic and ultrastructural degenerative changes in their subscapularis tendon and joint capsule than patients with post-traumatic recurrent shoulder i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…The strengths of the study include the fact that the biopsies were obtained from living humans and that efforts were made to reduce the inherent age difference between the study groups. The age difference was inevitable, but the fact that age has not been shown to be a source of bias when comparing fibril diameters in both the hip and the shoulder in previous publications must be taken into account [ 8 , 15 ]. Furthermore, Gagliano et al have shown that the morphological and molecular characteristics of the hamstrings tendon were not influenced by age [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strengths of the study include the fact that the biopsies were obtained from living humans and that efforts were made to reduce the inherent age difference between the study groups. The age difference was inevitable, but the fact that age has not been shown to be a source of bias when comparing fibril diameters in both the hip and the shoulder in previous publications must be taken into account [ 8 , 15 ]. Furthermore, Gagliano et al have shown that the morphological and molecular characteristics of the hamstrings tendon were not influenced by age [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Each element can obtain between 0 and 3 points. This procedure and evaluation system have been performed in multiple previous studies [ 3 , 8 , 15 , 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Participants of the pain group were volunteers recruited during their visit to a medical center. Participation had to meet the following criteria: (i) Presence of shoulder pain and painful arc for 15 days up to three months (subacute stage), as longer duration is expected to have degenerative changes [19], (ii) impingement syndrome after physical examination at the site of treatment with musculoskeletal ultrasound (Sonoline G20), (iii) diagnosis of impingement syndrome and not joint arthritis (AC, Shoulder), (iv) clinical signs of nerve pressure or any red flag of other pathology, (v) no sign of neurological deficit, spine trauma, or surgery to the cervical or shoulder area, (vi) absence of rheumatic or infectious diseases, psychiatric or cancer history, metabolic diseases (diabetes or thyroid), coagulopathies or use of anticoagulants, and neuromuscular degenerative diseases, and (vii) presence of painful arc on the movement of the shoulder and to be positive for an anterior slide test, apprehension test, and Hawkin's test or impingement sign [20]. Patients had a different clinical picture, but they all had to have pain on the suprascapular tendon and a positive sign on the supraspinatus tendon.…”
Section: Methodsmentioning
confidence: 99%
“…Afterwards, the slides were examined microscopically and the histological evaluation was performed in a blind fashion on coded samples, and a comparison was made with the sections from the control-treated group. Histological evaluation to assess integrity and organization of collagen fibers was based on 0–3 scale ( 35 , 36 ). Collagen integrity scores: 0 = continue, long fiber, 1 = slightly fragmented, 2 = moderately fragmented, 3 = severely fragmented.…”
Section: Methodsmentioning
confidence: 99%